Magnetic resonance susceptibility weighted phase imaging for the assessment of reperfusion intramyocardial hemorrhage. Issue 3 (14th June 2013) - Goldfarb, James W.; Hasan, Usama; Zhao, Wenguo; Han, Jing
<x xml:space="preserve">Abstract</x> Purpose To quantitatively investigate myocardial phase in multiple‐gradient‐echo images to determine normal phase angle ranges as a function of echo time and anatomical position and then compare phase values from patients with myocardial infarction with those normal ranges to determine the feasibility of intramyocardial hemorrhage detection. Methods Fifteen normal control and 11 patients with reperfused myocardial infarction participated in this prospective study. A 1.5 T magnetic resonance system was used to perform volumetric CINE, high‐pass filtered (HPF) phase, T2‐weighted, T2*‐weighted and late gadolinium‐enhanced infarct imaging at four times points after myocardial infarction. HPF‐phase analyzed using a 16‐segment model was compared with late gadolinium‐enhanced infarct imaging and T2* measurements. Results Myocardial HPF‐phase angle in the normal control group was small (−0.008 ± 0.027 radians). There was a difference between anatomical segments, with less variation in septal segments compared with cyclic variations in non‐septal segments. Abnormal phase was only shown in myocardial segments with transmural late gadolinium‐enhanced and microvascular obstruction consistent with intramyocardial hemorrhage. There were six studies from three patients (seven segments at 3 days, five segments at follow‐up) with HPF‐phase outside of normal range indicative of intramyocardial hemorrhage. Conclusion Myocardial HPF‐phase angle is normally small and varies by anatomical myocardial segment. intramyocardial hemorrhage causes a phase decrease beyond normal variations. Magn Reson Med 71:1210–1220, 2014. © 2013 Wiley Periodicals, Inc.